Meta-analysis of reconstruction techniques after low anterior resection for rectal cancer - Hüttner, Felix; Tenckhoff, Solveig; Jensen, Katrin; Uhlmann, Lorenz; Kulu, Yakup; Büchler, Markus W.; Diener, Markus K.; Ulrich, Alexis (The British journal of surgery, 2015)
Background Options for reconstruction after low anterior resection (LAR) for rectal cancer include straight or side-to-end coloanal anastomosis (CAA), colonic J pouch and transverse coloplasty. This systematic review compared these techniques in terms of function, surgical outcomes and quality of life. Methods A systematic literature search (MEDLINE, Embase and the Cochrane Library, from inception of the databases until November 2014) was conducted to identify randomized clinical trials comparing reconstructive techniques after LAR. Random-effects meta-analyses were carried out, and results presented as weighted odds ratios or mean differences with corresponding 95 per cent c.i. A network meta-analysis was conducted for the outcome anastomotic leakage. Results The search yielded 965 results; 21 trials comprising data from 1636 patients were included. Colonic J pouch was associated with lower stool frequency and antidiarrhoeal medication use for up to 1 year after surgery compared with straight CAA. Transverse coloplasty and side-to-end CAA had similar functional outcomes to the colonic J pouch. No superiority was found for any of the techniques in terms of anastomotic leak rate. Conclusion Colonic J pouch and side-to-end CAA or transverse coloplasty lead to a better functional outcome than straight CAA for the first year after surgery.
Gesehen am 03.06.2020